VIABILITAS Lactobacillus sp F213 PADA MINUMAN RICE JUICE (Oryza sativa) SELAMA PENYIMPANAN SUHU DINGIN (4°C) - Putra, I Gusti Putu Bhuana Aristya; Duniaji, Agus Selamet; Nocianitri, Komang Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 1 (2020): Jurnal ITEPA, 2020)
Lactobacillus sp F213 (LbF213) is a lactic acid bacteria isolated from a healty infant feces, which has been proven as a probiotic bacteria because it is resistant to low pH, bile salts, digestive enzymes, able to survive and colonize the intestine, and prevent infection from E.coli pathogens.This study was conducted to know the viability of Lactobacillus sp F213 probiotic bacteria in rice juice during cold storage and its effect on the characteristics of rice juice products. This study used a descriptive method in objective tests (total lactic acid bacteria test, total glucose, pH and total acid) and a complete randomized design method in the subjective test (sensory test). This study used two treatments, namely rice juice with the addition of Lactobacillus sp F213 and without the addition of probiotic bacteria which are then tested every 3 days of 0, 3, 6, 9 and 12 in cold temperature. The test results data presented in the way form of tables and figures. The results of this study indicate that the viability of Lactobacillus sp F213 to 12 days storage at cold storage temperatures. The addition of Lactobacillus sp F213 also tends not to affect the characteristics of rice juice during storage either from the results of pH, total acid and total glucose and from sensory characteristics such as color, aroma, taste and overall acceptance. Keywords: probiotics, rice juice, viability, Lactobacillus sp F213